Edukasi Perhitungan Harga Pokok Penjualan dalam Menetapkan Harga Jual Barang Dagang - Harya Ningsi, Etty; Lambok Manurung (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
This service provides education to the public regarding economic literacy among business actors, especially in terms of calculating the cost of goods sold (HPP) to determine the selling price of merchandise. The specific target of implementing this community service is to help people gain inadequate economic literacy. This often becomes an obstacle for the industry in managing business efficiently and is less profitable. The scope of service activities includes how to produce goods and services to strengthen the economy encourage business growth and create jobs. This service is carried out by educating the public on the basic concepts of calculating HPP, including raw material costs, labor costs, and overhead costs. Apart from that, an understanding of pricing strategies based on COGS is also provided to ensure decent profits. Keywords: Cost of Goods Sold, Economics, Education, COGS